A model of manufacturer-driven governing mechanisms and distributor performance - Harash J. Sachdev; Russell G. Merz (jbm - Journal of Business Market Management, 2012)
Drawing from relational exchange, dependence, and agency theories the authors explain that it is not only the type of governing mechanisms but also the proper sequencing of them that improves a manufacturer-distributor relationship and performance. Dependence affected relationship continuity positively. Monitoring affected the second order relational norm construct, comprising information sharing and flexibility, positively. Relational norm positively affected relationship continuity. Dependence, relationship continuity, monitoring, and relational norm affected distributor performance positively.
urn:nbn:de:0114-jbm-v5i1.56
Keywords: 650; agency theory; dependence; relational norm; monitoring distributor performance; relationship continuity